Analysis of blood metabolite characteristics at birth in preterm infants with bronchopulmonary dysplasia: an observational cohort study - Guo, Yanping; Chen, Jingjing; Zhang, Zhen; Liu, Chang; Li, Jiamin; Liu, Ying (Frontiers in Pediatrics, 2024)
Background: To analyze the characteristics of blood metabolites within 24 hours after birth in preterm infants with bronchopulmonary dysplasia (BPD) and to identify biomarkers for predicting the occurrence of BPD. Methods: Dried blood spots (DBS) were collected at birth from preterm infants with gestational age (GA) of less than 32 weeks in the cohort. The infants were divided into the BPD group and non-BPD group based on whether they eventually developed BPD. Dried blood spot filter papers were prepared from venous blood collected within the first 24 hours of life. Metabolites were measured using liquid chromatography-tandem mass spectrometry (LC-MS/MS) and analyzed using the R software package. Results: DBS samples from 140 infants with the GA< 32 weeks were used in the study, with 4 infants who died being excluded. Among the remaining 136 preterm infants, 38 developed BPD and 98 did not. To control for GA differences, we conducted a subgroup analysis. In the GA 24 +4 to 27 +6 weeks subgroup, we observed a significant decrease in histidine levels and the ornithine/citrulline ratio in the BPD group. Additionally, the ratios of acylcarnitines C3/C0 and C5/C0 were also significantly reduced. Conclusions: Metabolic markers in DBS within 24 hours after birth are promising for predicting the occurrence of BPD in preterm infants with GA< 28 weeks.